2019
DOI: 10.1055/s-0039-1694021
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis: Pathophysiology of Lung Disease

Abstract: Cystic fibrosis (CF) is a common, life-threatening, multisystemic, autosomal recessive disorder. In the last few years, giant steps have been made with regard to the understanding of CF pathophysiology, allowing the scientific community to propose mechanisms that cause the myriad of CF clinical manifestations. Following the discovery of the cystic fibrosis transmembrane conductance regulator (CFTR) gene in 1989, the structure and function of the CFTR protein were described. Since then, more than 2,000 variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 128 publications
(171 reference statements)
0
55
0
3
Order By: Relevance
“…When comparing the tomography of September 2019 with the tomography of April 2020 (Fig. 2), we found that both present chronic lesions typical of cystic fibrosis and patches of ground glass patches of subpleural distribution in the basal lobes, which corresponds to the process chronic inflammatory 2,9,15 .…”
Section: Discussionmentioning
confidence: 94%
“…When comparing the tomography of September 2019 with the tomography of April 2020 (Fig. 2), we found that both present chronic lesions typical of cystic fibrosis and patches of ground glass patches of subpleural distribution in the basal lobes, which corresponds to the process chronic inflammatory 2,9,15 .…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, this abnormally thick and sticky mucus layer entraps noxious agents and pathogens that initiate a persistent and self-perpetuating inflammatory response. This latter is recognized as a major driver of the progressive structural damage of the airways and lung parenchyma in CF patients, ultimately leading to bronchiectasis and respiratory failure [1].…”
Section: Introductionmentioning
confidence: 99%
“…The latter is very frequent in countries such as Peru where the prevalence of tuberculosis is high. Adults with CF may have a residual function of the gene involved in CF, and thus, the sweat chloride test with pilocarpine (gold standard test) is usually not positive, leading to indeterminate results (3,4), making molecular biology studies necessary to achieve a definitive diagnosis (1,5).…”
Section: Introductionmentioning
confidence: 99%
“…More than 2,000 mutations have been described in this gene, but only 412 mutations have been fully characterized (6). The different variations in mutations can be classified as: a) CF-causing variants, b) pathogenic variants of variable clinical significance, c) non-disease-causing variants, and d) variants of uncertain significance (3,4). The most frequent mutation worldwide is delta F508, although its presence varies considerably between races and regions.…”
Section: Introductionmentioning
confidence: 99%